2016
DOI: 10.17860/efd.91329
|View full text |Cite
|
Sign up to set email alerts
|

Bir Matematik Öğretmeninin İspat Kavrama Testine Dayalı Kendi Öğretim Uygulamasında Karşılaştığı Güçlükler ve Sürece Müdahale Yolları

Abstract: Öz: Son yıllarda matematiksel ispatlara verilen önemin artmasıyla birlikte, matematik sınıflarındaki muhakeme etme, ispat yapma ve tartışma durumları, matematik eğitimi araştırmaları için odak konular haline gelmiştir. İspat öğretiminde temel noktalardan birisi ispatın kavranmasıdır. İspatın kavranması sağlayan araçlardan birisi (ispat) kavrama testidir. Bu çalışma İspat Kavrama Testi'ne dayalı bir öğretim uygulamasını içeren geniş bir araştırmanın parçasıdır. Ana çalışma bir eylem araştırması olarak tasarlanm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…In Turkey, Yıldız (2006) conducted a proof comprehension test with four preservice mathematics teachers and analyzed their thoughts regarding the test. Another study on proof comprehension test was conducted by İnam & Uğurel (2016). The researchers investigated difficulties of teachers who conducted a PCT-based secondary school mathematics course, examining teachers' interventions and their effectiveness.…”
Section: Basis For the Studymentioning
confidence: 99%
“…In Turkey, Yıldız (2006) conducted a proof comprehension test with four preservice mathematics teachers and analyzed their thoughts regarding the test. Another study on proof comprehension test was conducted by İnam & Uğurel (2016). The researchers investigated difficulties of teachers who conducted a PCT-based secondary school mathematics course, examining teachers' interventions and their effectiveness.…”
Section: Basis For the Studymentioning
confidence: 99%
“…Although the proof and proving are expected to play much more important role in school mathematics, many research studies conducted in the last two decades have suggested that the students have serious difficulties with proof and proving (e.g., Bell, 1976;Chazan, 1993;Coe & Ruthven, 1994;Healy & Hoyles, 2000;İnam & Uğurel, 2016;Mariotti, 2000;Porteous, 1990;Romero, García, & Codina, 2015;Selden & Selden, 2009;Senk, 1985;Solomon, 2006;Sowder & Harel, 1998;Weber, 2001).…”
Section: Introductiomentioning
confidence: 99%
“…Alan yazın incelendiğinde matematiksel ispata yönelik öğretmen adaylarıyla yapılan pek çok çalışmaya rastlanmaktadır Güler & Ekmekci, 2016). Ancak öğretmenlerle yapılan çalışmaların oldukça sınırlı sayıda olduğu tespit edilmiştir (İnam & Uğurel, 2016). Ball, ThamesvePhelps (2008) özel alan bilgisinin önemine vurgu yaparak, bu kavramın yalnız öğretim ortamında kullanılabilecek alan bilgisi olarak ifade edilebileceğini belirtmiştir.…”
Section: Introductionunclassified